The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000052934
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Reproduction with Increased Abortion Rate in Transgenic Mice That Overexpress 15-Lipoxygenase

Abstract: 15-Lipoxygenase (15-LOX) is a lipid-oxidizing enzyme that is involved in cell cycle regulation. To evaluate the effect of 15-LOX on reproduction, we studied transgenic mice that overexpress 15-LOX. The transgene was introduced over the genetic background of the low density lipoprotein receptor deficient mice (LDL-R–/–) and reproduction was compared to LDL-R–/– mice. We found a lower pregnancy rate in the 15-LOX/LDL-R–/– mice as compared to the LDL-R–/– mice (62.74 vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The alkynylpurines 9 were synthesized by Sonogashira coupling and deprotected under standard acidic conditions (Scheme 2). The allene oxide 11a was obtained directly after deprotection of compound 9a by a "disfavored" 3-exo-dig cyclization, [12] and the elusive 10a could not be isolated. NOESY spectroscopy showed that the (Z)-isomer was formed and that cyclization under acidic conditions resulted in an intramolecular anti-addition of the hydroxy group.…”
Section: Resultsmentioning
confidence: 99%
“…The alkynylpurines 9 were synthesized by Sonogashira coupling and deprotected under standard acidic conditions (Scheme 2). The allene oxide 11a was obtained directly after deprotection of compound 9a by a "disfavored" 3-exo-dig cyclization, [12] and the elusive 10a could not be isolated. NOESY spectroscopy showed that the (Z)-isomer was formed and that cyclization under acidic conditions resulted in an intramolecular anti-addition of the hydroxy group.…”
Section: Resultsmentioning
confidence: 99%
“…In our study of biological activities of cytokinins and synthetic analogs [1Ϫ4], we identified certain 6-alkenyland 6-alkynylpurines as potent inhibitors of 15-lipoxygenase (15-LO) from soybeans [3]. The active compounds did not exhibit significant scavenging of the radical diphenylpicrylhydrazyl (DPPH) and we proposed that the purine derivatives were so-called non-antioxidant inhibitors; they exert their activity by a direct interaction with the enzyme.15-LO has been implicated in oxidation of low-density lipoproteins (LDL), a process believed to be important for the development of atherosclerosis [5,6], as well as for instance in prostate cancer [7,8], and spontaneous abortions [9]. Even though the clinical importance of these effects in humans is currently not known, development of potent and selective inhibitors of 15-LO appears to be an important task.…”
mentioning
confidence: 99%